Love and devotion - Nitya Chaitanya, Yati, 1924- (East-West University of Brahmavidya, 1979)
Study with examples from the Gītagovinda of Jayadeva, 12th cent. Sanskrit poet and poems of St. John of the Cross, 1542-1591.